The Study of CNS Manifestations in Aluminium Phosphide Poisoning - Khurana, Puneet; Gupta , Anju (Journal of Indian Academy of Forensic Medicine, 2015)
With rapid development in the field of science & technology and green revolution in the  agricultural sector, the problem of acute aluminium phosphide poisoning leading to morbidity and mortality  is spreading like a wild fire. Different disciplines of medical science are working on various aspects both  from treatment as well as preventive point of view. Aluminium Phosphide is a very toxic, cheap, ideal  suicidal and lethal protoplasmic poison involving all generations and organ systems of the body. Although  its incidence was unknown before 1980 but now it has surpassed every other poisoning in India  especially in the northern states and has created havoc with the human lives. Our study showed that  males (1.94:1) are the major sufferer with high mortality rate (76%). The freshness of tablet and lack of  specific antidote are directly related to its poor prognosis. Major CNS manifestations are dizziness (52%)  and headache (44%). Loss of consciousness is only the terminal event and sufficient time is available to  record the dying declaration. Magnesium sulphate has some role in its management.
Keywords: Aluminium Phosphide Poisoning; CNS Manifestations; Sensorium of the Patient